Legal sociology in the system of legal sciences - Hoang, Thi Kim Que (ĐHQGHN, 2017)
Legal sciences (studies of law) are a comprehensive knowledge system of the state and law, expressing themselves through a synthesis of notions, categories and rules of the movements and developments of the state and law. In the great system of legal sciences in Vietnam, legal sociology, in spite of its new formation, plays a remarkable role. The question of carrying out extensive researches on legal sociology has only been raised up in our country recently. However, it is better late than never! The fact is that only when legal sociology is seen as a separate branch of science can legal sciences themselves carry out researches on several matters of legal sociology. In Vietnam, a lawyer might also be at the same time a sociologist. That is, any notions and phenomena studied in law are inseparable from the social basis and social factors which require, supervise, and criticise legal rules and their corresponding activities of the state.